2005
DOI: 10.1007/s00520-005-0802-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between “malfunctioning events” and catheter-related infections in pediatric cancer patients bearing tunneled indwelling central venous catheter: results of a prospective observational study

Abstract: Malfunctioning events followed by catheter related infections and catheter related infections followed by malfunctioning are both rare events in children with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Although MD (71% of complications, 0.36 MD/1000 catheter‐days) was frequent in our series, the rate was within the range of previously published pediatric cohorts: Perdikaris et al reported 0.38 occlusions/1000 ICVC days, and other studies reported a mechanical complication rate of 0.45 per 1000 catheter‐days and 0.44 per 1000 catheter‐days . It must be emphasized that our MD definition was broader than those used by other authors.…”
Section: Discussionsupporting
confidence: 59%
“…Although MD (71% of complications, 0.36 MD/1000 catheter‐days) was frequent in our series, the rate was within the range of previously published pediatric cohorts: Perdikaris et al reported 0.38 occlusions/1000 ICVC days, and other studies reported a mechanical complication rate of 0.45 per 1000 catheter‐days and 0.44 per 1000 catheter‐days . It must be emphasized that our MD definition was broader than those used by other authors.…”
Section: Discussionsupporting
confidence: 59%
“…Twelve studies 59,61,66,67,72,76,82,83,89,97,105,121 described the outcome of CVADassociated BSI without the clarity and rigor of benchmarked standards, which meant that their CVAD-associated BSI data were not included in the review. Two studies 30,116 provided combined "all-type" infection or mechanical failure outcomes, instead of providing separated local and systemic infection, occlusion, and dislodgement data.…”
Section: Study Qualitiesmentioning
confidence: 99%